Prince Lestat - Rice, Anne (New York Alfred A. Knopf, 2014)
"The novel opens with the Vampire world in crisis ... vampires have been proliferating out of control; burnings have commenced all over the world, huge massacres similar to those carried out by Akasha in The Queen of the Damned ... Old vampires, roused from slumber in the earth are doing the bidding of a Voice commanding that they indiscriminately burn vampire-mavericks in cities from Paris and Mumbai to Hong Kong, Kyoto and San Francisco. As the novel moves from present day New York and the West Coast to Ancient Egypt, fourth century Carthage, 14th century Rome, the Venice of the Renaissance, the worlds and beings of all the Vampire Chronicles--from Louis de Pointe du Lac, the eternally young Armand whose face is that of a Boticelli angel; Mekare and Maharet, Pandora and Flavius; David Talbot, vampire and ultimate fixer from the Secret Talamasca, and Marius, the true child of the Millennia; along with all the other new seductive, supernatural creatures--come together in this large, luxuriant, fiercely ambitious novel to ultimately rise up and seek out who--or what--The Voice is, and to discover the secret of what it desires and why ... And, at the book's center, the seemingly absent, curiously missing hero-wanderer, the dazzling, dangerous rebel-outlaw--the great "hope" of the Undead, the dazzling Prince Lestat."--
Keywords: Vampires; Fiction -- Occult & Supernatural; Fiction -- Fantasy -- Paranormal; Fiction -- Suspense; Horror fiction; Paranormal fiction; Fiction